(untitled) (Scientific journal of the Fergana State University, 2023)
In this article a wide range of museum activities and their roles with regard to implementation of cultural heritage among people through establishing these activities in museums are enormously discussed. Two methods are used to gather information on specific research area. The first method is interview with museum curators and marketers, the second one is questionnaire survey with visitors. Main suggestions can be obtained from the research; a wide variety of museum activities are enlightened in this article, museum curators can use these implementation tools to improve the social status of museums among people. Museum activities should be more engaging and innovative in digital era to attract a large number of visitors. The majority of museums are currently adopting to unexpected changes and innovative ideas of the modern world. This paper may help the researchers and museum curators to establish new implement tools while making communication with museum-goer.